2021
DOI: 10.1001/jamaoncol.2021.4960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Toxic Effects of Single-Agent Immune Checkpoint Inhibitors Among Patients Aged 80 Years or Older With Cancer

Abstract: IMPORTANCE Geriatric (aged Ն80 years) patients are historically underrepresented in cancer clinical trials. Little is known about the efficacy of immune checkpoint inhibitors (ICIs) in geriatric patients. These agents are associated with immune-related adverse events (irAEs), which may be particularly associated with morbidity in this population.OBJECTIVE To provide insight into the clinical outcomes and safety of ICIs among geriatric patients (aged Ն80 years) with cancer. DESIGN, SETTING, AND PARTICIPANTSA Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 15 publications
8
63
1
1
Order By: Relevance
“…3 However, a multicenter, retrospective study of 928 geriatric patients with various tumors (NSCLC, melanoma, genitourinary) treated with single-agent ICIs also reported that the rate of grade ≥3 immune-related events was 12.2%. 21 In addition, grade ≥3 adverse events in a pooled analysis of elderly patients with advanced NSCLC (≥75 years) treated with pembrolizumab was 24.2%, which is higher than that of our study. Furthermore, one patient developed grade 5 pneumonitis in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…3 However, a multicenter, retrospective study of 928 geriatric patients with various tumors (NSCLC, melanoma, genitourinary) treated with single-agent ICIs also reported that the rate of grade ≥3 immune-related events was 12.2%. 21 In addition, grade ≥3 adverse events in a pooled analysis of elderly patients with advanced NSCLC (≥75 years) treated with pembrolizumab was 24.2%, which is higher than that of our study. Furthermore, one patient developed grade 5 pneumonitis in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Immune checkpoint blockade therapy has been hugely successful with effective results in many cancer types [ 114 , 115 , 116 ], acting through reinforcement of T cell function and improving the cytotoxic capacity against cancer cells [ 1 ]. In this section, we summarize existing research examining the contributions of CXCL13/CXCR5 to immunotherapy in preclinical models ( Table 1 ).…”
Section: The Cxcl13/cxcr5 Signaling Axis In the Ici Response Of Preclinical Modelsmentioning
confidence: 99%
“…The study was reported in JAMA Oncology. 1 In this study, researchers retrospectively analyzed the outcomes of 928 patients at 18 academic medical centers across the United States and Europe who had cancer, were aged 80 years or older, and were treated with single-agent ICIs. The researchers primarily reviewed 3 types of cancer: non-small cell lung cancer; melanoma; and genitourinary tumors, including prostate, bladder, and kidney cancer.…”
Section: Findings In Contextmentioning
confidence: 99%
“…A new analysis from the trial shows that patients with advanced renal cell carcinoma who received nivolumab and ipilimumab experienced better treatment-free survival (TFS) over a 42-month period than patients who received the targeted therapy sunitinib, regardless of their International Metastatic Renal Cell Carcinoma Database Consortium risk group. 1 "We have been working to define a novel endpoint for clinical trials termed TFS, or treatment-free survival. TFS measures the durable effects, both good [treatment response] and bad [side effects], of cancer therapy," says the study's principal investigator, David McDermott MD, chief of medical oncology at Beth Israel Deaconess Medical Center and leader of the Kidney Cancer Program at Dana-Farber/Harvard Cancer Center in Boston, Massachusetts.…”
Section: Findings In Contextmentioning
confidence: 99%